A study of microstructure and mechanical properties of aluminum alloy using laser cleaning. (June 2019) - Shi, Tianyi; Wang, Chunming; Mi, Gaoyang; Yan, Fei
Abstract: In this study, laser cleaning of aluminum alloy was investigated adopting a 120 W MOPA pulsed fiber laser. The results show that laser cleaning can remove the oxide layer on the surface of aluminum alloy effectively. The ring-shaped cater was generated on the surface because of the metal vapor recoil pressure. The hardened layer easily formed on the surface of Al matrix by plastic deformation. The O and Mg elements decreased significantly after laser cleaning. It indicated that the oxide layer on the surface of aluminum alloy can be quickly eliminated, which availably improved the tensile and bending properties. Laser cleaning technology can be widely applied in the field of manufacturing and satisfy the industrial requirements.